2005
DOI: 10.1007/s10534-005-3712-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Periplasmic Ferric-hydroxamate Binding Protein FhuD

Abstract: FhuD is a periplasmic binding protein (PBP) that, under iron-limiting conditions, transports various hydroxamate-type siderophores from the outer membrane receptor (FhuA) to the inner membrane ATP-binding cassette transporter (FhuBC). Unlike many other PBPs, FhuD possesses two independently folded domains that are connected by an alpha-helix rather than two or three central beta-strands. Crystal structures of FhuD with and without bound gallichrome have provided some insight into the mechanism of siderophore b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
3
28
0
1
Order By: Relevance
“…3B) according to the nomenclature introduced by Clancy et al (12), who studied siderophore-dependent iron acquisition of a group B streptococcus. We refrained from using the pia gene nomenclature introduced by Brown et al (9) because the fhu designation specifically refers to ferric hydroxamate uptake, which we introduced for E. coli (26) and has been used since then for gram-negative and gram-positive bacteria (5,8,30,31). spr0937 is an open reading frame on the cDNA strand and is probably not related to ferrichrome transport.…”
Section: Resultsmentioning
confidence: 99%
“…3B) according to the nomenclature introduced by Clancy et al (12), who studied siderophore-dependent iron acquisition of a group B streptococcus. We refrained from using the pia gene nomenclature introduced by Brown et al (9) because the fhu designation specifically refers to ferric hydroxamate uptake, which we introduced for E. coli (26) and has been used since then for gram-negative and gram-positive bacteria (5,8,30,31). spr0937 is an open reading frame on the cDNA strand and is probably not related to ferrichrome transport.…”
Section: Resultsmentioning
confidence: 99%
“…However, the TonB-binding surface on FhuD as identified by phage display both overlaps the siderophore-binding site and extends beyond it; competition would not be expected. Furthermore, there is no evidence to suggest large conformational changes in FhuD upon binding siderophore (19). In the siderophore-bound state, FhuD probably maintains a rigid backbone; this rigidity would not influence binding of TonB.…”
Section: Discussionmentioning
confidence: 98%
“…If there was a continuous landscape of all four regions, it would require a displacement of loop 3 from FhuD to accommodate TonB binding. Recent molecular dynamics simulations on the FhuD structure (19) indicated that the C-terminal domain of FhuD has more overall mobility than the N-terminal domain. However, within the relatively static N-terminal domain, loop 3 was observed to be the most mobile region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, while the two domains of these proteins are usually linked by flexible antiparallel ␤-strands, which are also found in ferric ion binding proteins such as FbpA (235), SfuA, and YfuA (301), belonging to the transferrin structural superfamily, the bidomains of FhuD and CeuE are connected via ␣-helical elements, making their backbones more rigid, and abolish broad conformational changes upon ligand binding. However, molecular dynamic simulations suggested a 6°clo-sure of the FhuD C-terminal domain upon ferrichrome release, and this motion might lead to FhuD conformers that could selectively interact with the FhuB transmembrane component of the transporter (177). The ligand binding site is commonly the most variable part in periplasmic binding protein structures and can be used for phylogenetic classification as in the case of periplasmic ferric ion binding proteins that are currently divided into three classes depending on their coordination modes for the Fe(III) ligand (301).…”
Section: General Steps Of Siderophore Pathwaysmentioning
confidence: 99%